Los rincones de lectura en el proceso enseñanza aprendizaje para los estudiantes de Básica Superior en el periodo 2016-2017. - Bonilla Baño, Zoila Adriana (2018)
The research work was intended to know the problem by not having the reading corners, in the 8th "B" at "Su Cambio por el Cambio " Educational Center in the period 2016-2017, the present research shows a diagnosis that will contribute to future research which will provide its usefulness in a manner appropriate for the implementation of reading corners in the classroom. The objective of this research is to determine the importance of reading corners, to improve the teaching-learning process which allows to take autonomous decisions on the students, the present research methodology was applied deductive, inductive methods, also applied the techniques such as the interview with its guide questions, the survey with its instrument the questionnaire; to establish the lack of reading corners and giving this as the result of the lack of comprehension in reading. The research generated a practical contribution that is to establish important date regarding the lack of reading corners in the classroom, has a social impact since the lack of reading corners is a latent risk in the teaching-learning process of the students as a result teachers should provide appropriate support to give solutions and encourage reading in learning . The present research work was important to known what were the causes of not having a reading corner that affects adolescents nowadays and provide solutions that improve the reading skills and form an optimal environment and better reading habits in each student what could be the possible solutions to help improve reading ability and form an optimal environment with good habits of reading in each student.